Critical analysis of the restoration of the House of Osambela, 1981, Lima - Vasquez Gutierrez, Martha Elena (2018)
In 1981, a comprehensive restoration project was carried out at the Casa de Osambela. It had, in those years, a positive impact on the Lima community because, thanks to its new use as the Inca Garcilaso de la Vega Cultural Center, it fostered a space of social interaction and cultural exchange that strengthened the cultural identity of those citizens of Lima. Thus, it is important to analyze the theoretical and methodological aspects that were employed in the project of restoring and assigning new uses to this remarkable building, and how those relate to the theoretical criteria of restoration for the protection of immovable heritage established in international documents. Through critical analysis, we seek to recognize the contributions and shortcomings of this restorative intervention, and how it contributed to the preservation and revaluation of immovable cultural heritage.